Knowledge, Attitude, and Practice Toward COVID-19 Among Sherubtse College Students in Bhutan: A Web-Based Cross-Sectional Study - Dorji, Thinley; Wangmo, Karma; Yezer,; Wangchuk, Tashi; Tshokey,; Wangdi, Kinley (Frontiers in Public Health, 2021)
Bhutan has reopened schools and colleges after an initial closure to contain coronavirus disease 2019 (COVID-19) transmission. However, the risk of transmissions is higher in the schools and colleges due to crowding. Therefore, this study aimed to assess the level of knowledge, attitude, and practice (KAP) toward COVID-19 among the students of Sherubtse College in Bhutan. A cross-sectional study using a questionnaire was conducted in September 2020 among the students of Sherubtse College, Bhutan. The questionnaire was made in the Google Forms and administered through a social forum WeChat app. The KAP scores were calculated that include mean scores. The association between the KAP was assessed using the Pearson's correlation coefficient. A total of 613 students participated in the survey. The majority of the participants (57%) were female and 56% were from the third year. The mean knowledge score was 10.7 (SD = 1.7; range 0–14), mean attitude score of 3.67 (SD = 1.0; range: 0–5), and mean practice score of 5.19 (SD = range: 0–6). A majority of the students had good knowledge (98%) and practice (93.5%) scores, and a positive attitude (86.6%) toward COVID-19. A positive but weak correlation between good knowledge and practice (r = 0.1, p = 0.0126) was observed. Having a positive attitude led to practicing appropriately most of the time (r = 0.1866, p < 0.001). The students had good KAP scores and followed the COVID-19 prevention protocols advocated by the government. Good knowledge and a positive attitude were translated into good practice. Therefore, the education campaign of the Bhutan government seems to be effective in the students.